2020
DOI: 10.1097/aco.0000000000000939
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative delirium – treatment and prevention

Abstract: Purpose of review Postoperative delirium (POD) is one of the most severe complications after surgery. The consequences are dramatic: longer hospitalization, a doubling of mortality and almost all cases develop permanent, yet subtle, cognitive deficits specific to everyday life. Actually, no global guideline with standardized concepts of management exists. Advances in prevention, diagnosis and treatment can improve recognition and risk stratification of delirium and its consequences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 26 publications
0
34
0
1
Order By: Relevance
“…[ 8 , 9 ] Postoperative delirium can exacerbate the condition and increase the risk of pulmonary infections, electrolyte disturbances, deep vein thrombosis, and falls, thus prolonging the length of hospital stay, increasing the cost, and burdens of patients and society. [ 10 , 11 ] It is been reported that the mortality of patients with delirium after hip fracture surgery increased by about 3 times compared with patients without delirium in 6 months after surgery. [ 12 ] Therefore, the management of delirium after hip fracture surgery is essential to the prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 , 9 ] Postoperative delirium can exacerbate the condition and increase the risk of pulmonary infections, electrolyte disturbances, deep vein thrombosis, and falls, thus prolonging the length of hospital stay, increasing the cost, and burdens of patients and society. [ 10 , 11 ] It is been reported that the mortality of patients with delirium after hip fracture surgery increased by about 3 times compared with patients without delirium in 6 months after surgery. [ 12 ] Therefore, the management of delirium after hip fracture surgery is essential to the prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The latter data suggest that perioperative complications should include acute medical conditions in addition to surgical ones in aged. Moreover, in older adults a further severe complication should be considered after surgery, that is post-operative delirium [ 4 ]. Its consequences are longer hospitalisation, a doubling of mortality and almost all cases develop permanent, yet subtle, cognitive deficits specific to everyday life [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in older adults a further severe complication should be considered after surgery, that is post-operative delirium [ 4 ]. Its consequences are longer hospitalisation, a doubling of mortality and almost all cases develop permanent, yet subtle, cognitive deficits specific to everyday life [ 4 ]. In 2018, Eamer et al [ 5 ] reviewed risk assessment tools in studies on elderly surgical patients, and they concluded that the majority of them are not commonly used for pre-operative risk assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, corresponding measures should be taken to modify risk factors, such as reducing perioperative blood loss [31,32], shortening the duration of anesthesia and surgery as much as possible, controlling in ammatory reactions to reduce the level of in ammatory factors [33][34][35]. In addition, for hyperactive delirium, the risk factor is pain, for which appropriate management could be taken to relieve the pain of the patients [36][37][38][39]. For hypoactive delirium, preoperative use of β-blocker drugs can signi cantly reduce the incidence of hypoactive delirium after surgery.…”
Section: Discussionmentioning
confidence: 99%